THE INTERRELATIONSHIP OF INNOVATION, DIGITAL TRANSFORMATION AND SUSTAINABLE DEVELOPMENT (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2026)
This article analyzes the theoretical foundations of the concepts of innovation, digital transformation, and sustainable development, as well as their interrelationships. It also discusses the role of these processes in the development of the modern economy and society, the impact of digital technologies on sustainable development, and their prospects in the conditions of Uzbekistan.